Inhibitory effect of hop fractions against Gram-positive multi-resistant bacteria. A pilot study - Bogdanová, Kateřina; Kolář, Milan; Langová, Kateřina; Dušek, Martin; Mikyška, Alexandr; Boštíková, Vanda; Boštík, Pavel; Olšovská, Jana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2018)
AIM: Our research focused on the antimicrobial effects of purified hop (Humulus lupulus L.) fractions including α-bitter acids (humulones), β-bitter acids (lupulones) and xanthohumol, and a commercial CO2 hop extract of bitter acids against reference and multi-resistant strains of Gram-positive and Gram-negative bacteria and against selected yeast strains. METHODS: In vitro testing of antimicrobial activity was performed according to standard testing protocols (EUCAST). The effects of hop extracts on bacterial/yeast strains at concentrations below MICs were also determined and the antimicrobial potential of hop extracts was compared with selected antibiotics using optical density measurement. RESULTS: The fractions were effective not only against reference strains of Gram-positive bacteria but, more importantly, against their methicillin- and vancomycin-resistant variants. No antimicrobial effect was detected against Gram-negative bacterial strains. Among the tested substances, xanthohumol was identified as the hop fraction with the most potent antimicrobial properties. It was also found that hop substances exerted their antimicrobial effects at concentrations considerably lower than the determined MICs, with the strongest effect in case of α-bitter acids in enterococci. CONCLUSION: The search for and research of new compounds with antimicrobial properties represents a possible solution to the current global problem of bacterial resistance. Our data suggest a desirable activity of hop fractions against some multi-resistant bacterial strains. Thus, hops might find use as a source of potential antimicrobial agents applicable in both human and veterinary medicine.
Keywords: Plant Extracts; rostlinné extrakty; Drug Resistance, Multiple, Bacterial; Microbial Sensitivity Tests; lidé; Gram-Negative Bacteria; gramnegativní bakterie; antiinfekční látky; mikrobiální testy citlivosti; Pilot Projects; Anti-Infective Agents; pilotní projekty; mnohočetná bakteriální léková rezistence; Humulus; Humans